An experimental study on the temperature and structural behavior of a concrete wall exposed to fire after a high-velocity impact by a hard projectile. (July 2017) - Morita, Takeshi; Beppu, Masuhiro; Suzuki, Makoto
Abstract: Projectiles, such as turbine blades, can be released in an accident and impact structures. Airplanes and other flying objects can also become impact projectiles. These impacts occasionally cause fire when fire loads, such as oil, fuel, and other combustible materials, are present. This study examines the thermal insulation performance of concrete plates and the structural fire behavior of load-bearing reinforced concrete walls that are exposed to fire after a high-velocity impact by a hard projectile. Impact and fire tests were carried out using small-scale concrete plates and reinforced concrete walls. The results show the influence of local damage and the advantage of short-fiber reinforced concrete subjected to impact loads and fire.